2009
DOI: 10.1165/rcmb.2007-0438oc
|View full text |Cite
|
Sign up to set email alerts
|

16,16-Dimethyl Prostaglandin E2 Efficacy on Prevention and Protection from Bleomycin-Induced Lung Injury and Fibrosis

Abstract: In this study, we evaluated the protective effect and therapeutic potential of the prostaglandin E(2) (PGE(2)) synthetic analog 16,16-dimethyl-PGE(2) (dmPGE(2)) in the animal model of pulmonary fibrosis induced by bleomycin. Mice subjected to intratracheal administration of bleomycin (1 mg/kg) received a dmPGE(2) dose of 30 microg/kg/day by continuous subcutaneous infusion. Bronchoalveolar lavage (BAL); immunohistochemical analysis for IL-1, TNF-alpha, and nitrotyrosine; measurement of fluid content in lung; m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 41 publications
5
30
1
Order By: Relevance
“…It is thus possible that PGE 2 is more likely to be detected in BALF, and prostacyclin would more likely be detected in other compartments, such as urine. Another relevant study that should be noted is the one by Failla and coworkers (17), which showed that treatment with the PGE 2 analog, dmPGE 2 , protects mice from bleomycin-induced pulmonary inflammation and fibrosis (17). Although this study utilized a similar experimental protocol, there are key differences between their report and ours.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…It is thus possible that PGE 2 is more likely to be detected in BALF, and prostacyclin would more likely be detected in other compartments, such as urine. Another relevant study that should be noted is the one by Failla and coworkers (17), which showed that treatment with the PGE 2 analog, dmPGE 2 , protects mice from bleomycin-induced pulmonary inflammation and fibrosis (17). Although this study utilized a similar experimental protocol, there are key differences between their report and ours.…”
Section: Discussionmentioning
confidence: 85%
“…Considering the variability in bleomycin response in different mouse strains, this is an important experimental variable that should be taken into consideration. Finally, the most important difference between our study and the one by Failla et al (17) is that, in addition to examining the role of PGE 2 in the inflammatory, histological, and biochemical response to bleomycin, we also studied the effect of PGE 2 on lung function. Importantly, our data demonstrate significant protective effects of PGE 2 on this endpoint.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The relevance of such an impairment is suggested by the facts that pharmacologic (administration of indomethacin) (22) or genetic (gene deletion of Cox2) (23) reduction in PGE 2 synthesis in the lung as well as gene deletion of EP2 (24) augment bleomycin-induced fibrosis in mice. By contrast, protection against experimental fibrosis has been observed when endogenous PGE 2 is overproduced (21,25,26) or when exogenous PGE is administered (27). Interestingly, a reduction in PGE 2 responsiveness mediated by a loss of the EP2 receptor has also been described in fibroblasts derived from bleomycin-treated mice (24) and IPF patients (28).…”
Section: Introductionmentioning
confidence: 99%
“…Agents that increase cAMP levels inhibit various measures of pulmonary fibroblast function, including collagen synthesis, cell proliferation and migration, and collagen gel contraction (12,20,31). Administration of a ␤-adrenergic receptor (␤-AR) antagonist causes an elevation in pulmonary collagen, while treatment with PGE 2 , prostacyclin, or aminophylline [which increases cAMP via inhibition of phosphodiesterases (PDEs)] attenuates bleomycin-stimulated pulmonary fibrosis (10,23,24,29,33). Thus, agents working through the cAMP signaling cascade appear to have antifibrotic potential, but no therapies using these mechanisms have proven effective in humans.…”
mentioning
confidence: 99%